2020
DOI: 10.3390/jcm9103336
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Comorbidities in Korean Patients with Rosacea: Results from a Multi-Institutional Case-Control Study

Abstract: Recent evidence links rosacea to systemic disease, but there are not enough methodologic studies addressing this association in Asians. Our aim was to identify rosacea comorbidities in Koreans and establish a reference database. A multi-center, case-control study was performed where a total of 12,936 rosacea patients and 12,936 age- and sex-matched control subjects were identified from 2007 to 2018. Logistic regression was performed to find significant association between rosacea and Sjögren syndrome (odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 65 publications
2
18
2
Order By: Relevance
“…In a Korean study, Woo et al investigated the potential association of rosacea with autoimmune disorders, including Sjögren syndrome, systemic sclerosis, rheumatoid arthritis, ankylosing spondylitis, autoimmune thyroiditis, alopecia areata, and vitiligo. 13 They concluded that the risk of autoimmune thyroiditis increased solely in female patients with rosacea. Our study included female patients only and found that the anti-TPO antibody levels decreased as the severity of rosacea increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Korean study, Woo et al investigated the potential association of rosacea with autoimmune disorders, including Sjögren syndrome, systemic sclerosis, rheumatoid arthritis, ankylosing spondylitis, autoimmune thyroiditis, alopecia areata, and vitiligo. 13 They concluded that the risk of autoimmune thyroiditis increased solely in female patients with rosacea. Our study included female patients only and found that the anti-TPO antibody levels decreased as the severity of rosacea increased.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that serum anti‐TPO levels can be used as a marker in determining the severity of rosacea and may help the clinician predict the course of the disease. In a Korean study, Woo et al investigated the potential association of rosacea with autoimmune disorders, including Sjögren syndrome, systemic sclerosis, rheumatoid arthritis, ankylosing spondylitis, autoimmune thyroiditis, alopecia areata, and vitiligo 13 . They concluded that the risk of autoimmune thyroiditis increased solely in female patients with rosacea.…”
Section: Discussionmentioning
confidence: 99%
“… 60 64 Phase III trials of dupilumab consisted of 20–27% Asian individuals and 5–7% Black individuals; thus, the efficacy of dupilumab is consistent in diverse ethnic groups. 62 65 A subgroup analysis by race demonstrated comparable results between white, Black and Asian patients, although the number of Black individuals was limited. 63 , 65 For moderate-to-severe AD in patients 12 years and older, dupilumab is the only approved biologic.…”
Section: Treatmentmentioning
confidence: 92%
“… 62 65 A subgroup analysis by race demonstrated comparable results between white, Black and Asian patients, although the number of Black individuals was limited. 63 , 65 For moderate-to-severe AD in patients 12 years and older, dupilumab is the only approved biologic. 66 A recent study demonstrated the effectiveness of dupilumab in improving QOL of patients with AD amongst various racial subgroups (i.e.…”
Section: Treatmentmentioning
confidence: 92%
See 1 more Smart Citation